Comparison of PCR with stained slides of bone marrow and lymph nodes aspirates with suspect diagnosis for leishmaniasis - Santos, T. R.; Carreira, V. S. [UNESP]; Ferrari, H. F. [UNESP]; Moreira, M. A. B.; Luvizotto, Maria Cecília Rui [UNESP] (Elsevier B.V., 2014)
Visceral leishmaniasis (VL), also known as kala-azar, is a disseminated protozoan infection caused by Leishmania donovani complex. Traditionally the definite diagnosis is made by amastigote detection in the tissue. The aim this study was to evaluate the PCR technique in stained slides of bone marrow and lymph nodes aspirates with suspect diagnosis for leishmaniasis. Slides were selected totaling 62 suspect cases (33 bone marrow samples and 29 lymph node samples) and 17 positive cases (8 bone marrow and 9 lymph node). From 62 suspect cases, 39 (62.90%) were confirmed to be positive being 17 (n = 29) lymph node aspirates and 22 (n = 33) bone marrow. This finding is in agreement with the higher sensitivity of the PCR assay compared to direct microscopic observation. In conclusion, the findings of this study supports the use of PCR on archive cytological preparation stained slides for the diagnosis of canine visceral leishmaniasis, emphasizing the higher sensitivity of this technique when compared to direct microscopic examination and mostly the use of the suspect status for the cytology samples that presents the previously mentioned particularities with focus on detecting the oligosymptomatic or assymptomatic dogs in endemic areas functioning as potential reservoirs for this disease. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Canine leishmaniasis; PCR; Cytology; Bone marrow; Lymph node